2010
DOI: 10.1002/app.32948
|View full text |Cite
|
Sign up to set email alerts
|

Improved adhesion of TiO2‐based multilayer coating on HDPE and characterization of photocatalysis

Abstract: Multilayered photocatalytic TiO 2 -based coating was prepared by spin coating on a high-density polyethylene (HDPE) substrate. The multilayered coating consisted of a polyurethane (PU) barrier layer and two layers of TiO 2 nanoparticles bound with PU. The adhesion between the HDPE substrate and protective PU coating was enhanced by oxygen plasma treatment of the substrate. The improved adhesion contributed to the photocatalytic degradation of palmitic acid. Long-term activity of the photocatalytic coating in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…It finds use in a wide range of applications such as air purification, photoinduced hydrophilic coating and self-cleaning devices, self-sterilization, wastewater treatment, and production of hydrogen fuel . This is attributed to its unique properties like low cost, nontoxicity, relatively high photocatalytic activity (PCA) in ultraviolet (UV) light, high chemical stability, strong oxidizing power, and ready availability in the market. However, this potential to be fully utilized for commercial applications like water and wastewater treatment is greatly hindered by the costly and time-consuming post-treatment recovery of the fine particles. , To overcome this problem, extensive research is being carried out to immobilize TiO 2 on various substrates such as hollow glass spheres, reactor walls, inorganic carbon fabrics, glass mats, synthetic fabrics, natural fabrics, and polymers . Out of the various supports reported in the literature, it has been found that polymeric substrates are of great interest to researchers.…”
Section: Introductionmentioning
confidence: 99%
“…It finds use in a wide range of applications such as air purification, photoinduced hydrophilic coating and self-cleaning devices, self-sterilization, wastewater treatment, and production of hydrogen fuel . This is attributed to its unique properties like low cost, nontoxicity, relatively high photocatalytic activity (PCA) in ultraviolet (UV) light, high chemical stability, strong oxidizing power, and ready availability in the market. However, this potential to be fully utilized for commercial applications like water and wastewater treatment is greatly hindered by the costly and time-consuming post-treatment recovery of the fine particles. , To overcome this problem, extensive research is being carried out to immobilize TiO 2 on various substrates such as hollow glass spheres, reactor walls, inorganic carbon fabrics, glass mats, synthetic fabrics, natural fabrics, and polymers . Out of the various supports reported in the literature, it has been found that polymeric substrates are of great interest to researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalytic reaction using TiO2/UV can simultaneously treat organic compounds and metallic elements in addition to change non-biodegradable to biodegradable organic compounds. TiO2 is used as an effective, inexpensive and nontoxic photocatalyst for the degradation of synthetic dyes, oxidation cyanide and reduction of Cr(VI) [12][13].…”
Section: (A) (B)mentioning
confidence: 99%
“…Due to the outstanding of several advantages of polymer substrates, such as, flexibility in nature, mechanical and chemical stabilities, high durability, low cost and availability [29]; hence, it has been used as a support for TiO 2 photocatalyst. Recently, various types of polymeric materials used as the polymer-supported TiO 2 have shown promising performance for the photocatalysis, for example, polyaniline (PANI) [18], polyethylene terephthalate (PET) [9], silicone [28], polymethyl methacrylate (PMMA) [7] and high-density polyethylene (HDPE) [14]. Though, the methods or techniques to prepare the polymer-supported TiO 2 photocatalyst, such as, sol-gel and spin coating [16], dip and spin coating [3,4,36] and plasma layer deposition [17], are practically difficult and still have some disadvantages.…”
Section: Introductionmentioning
confidence: 99%